Effect of aerobic exercise on the improvement of executive function in children with attention deficit hyperactivity disorder: a systematic review and meta-analysis - Yang, Gao; Liu, Qiang; Wang, Wei; Liu, Wei; Li, Junfeng (Frontiers in Psychology, 2024)
Objective: This study aims to investigate the effect of aerobic exercise therapy on executive function in children with attention deficit hyperactivity disorder aged 6-12 years.We conducted a systematic review and meta-analysis using PubMed and Web of Science.The cut-off date was June 1, 2023. The aim was to assess the impact of aerobic exercise interventions on children with ADHD and all randomized controlled trials eligible for aerobic exercise interventions for children with ADHD were included. Nine randomized controlled trials were screened for eligibility for systematic evaluation, and the nine studies were assessed for risk of bias using the PEDro score and the GRADE Quality of Evidence Evaluation System for quality grading of outcome indicators. After testing for heterogeneity, a random-effects model or a fixed-effects model was selected for analysis. Finally, meta-analyses and regression analyses were performed on the core functions (inhibitory control,cognitive flexibility, and working memory) and subgroups of the nine studies on executive function using Revman 5.4 and Stata 16.0.The risk of bias evaluation showed a mean PEDro score of 7.78, and of the nine studies, two were rated as having excellent methodological quality, while the remaining seven had a good level of evidence, and the GRADE evidence evaluation showed that the outcome indicators were all of moderate quality. Inhibitory control [SMD=0.83,95% CI (0.37-1.29),Z=3.51,P=0.0005], cognitive flexibility [SMD=0.65,95% CI (0.37-0.93),Z=4.58,P<0.00001], and working memory [SMD=0.48,95% CI ( 0.02-0.95),Z=2.03, P=0.04] were statistically significant, with effect sizes of moderate or higher; furthermore, in subgroup analyses type of intervention, duration, intensity, and medication use had different effects on inhibitory control and cognitive flexibility, and the combined IC,CF statistic found that a single category of aerobic exercise (β=0.867,P<0.001),moderate intensity (β=0.928,P<0.001), 6-12 weeks (β=0.804,P<0.001), 60-90min (β=0.894,P<0.001), and the use of medication (β=1.202,P=0.002) were better for overall improvement in EF.Aerobic exercise therapy significantly improved executive functioning in children with ADHD, showing above moderate effect sizes especially in inhibitory control, cognitive flexibility, and working memory. Aerobic exercise therapy can be used as a reference in improving executive function in children with ADHD.